Cultural Shift and Adaptive Quality in Migrant Kashmiri Pandits - Bhan, Nikita; S. Bindra, Sukhwant (International Journal of Psychosocial Rehabilitation, 2020)
The conflict of 1989-90 in the Kashmir valley led to the migration of a large number of people belonging to the Hindu, Sikh, and Muslim communities to other parts of the country. These people have been categorized as migrants by the Indian government; however, they are also called internally displaced persons.The paper, however, focuses on the Kashmiri Pandits, i.e., the Hindu community of Kashmir. It tries to understand the changes in the culture of this community post-migration and how they have adapted themselves socially as well as emotionally with the host community in order to sustain themselves in a different environment. The displacement has altered their culture, especially the dressing, food habits, and festivals in particular, which were well rooted in the Kashmir valley, i.e., their homeland. Besides that, it also affected them emotionally to a great extent.The community did modify and change their culture, but at the same time they did manage to sustain some part of it.